Novel N-methylsulfonyl-indole derivatives: biological activity and COX-2/5-LOX inhibitory effect with improved gastro protective profile and reduced cardio vascular risks. (31st December 2023) - Philoppes, John N.; Abdelgawad, Mohamed A.; Abourehab, Mohammed A. S.; Sebak, Mohamed; A. Darwish, Mostafa; Lamie, Phoebe F.
Abstract: Three novel series of N -methylsulfonylindole derivatives 3a&b, 4a–e, and 5a–e were synthesised. Different biological activities of the synthesised compounds were studied. Antimicrobial activity showed that, compounds 4b, 4e and 5d had selective antibacterial activity against the Gram-negative bacteria, Salmonella enterica and/or E. coli . The anti-oxidant activity of the synthesised compounds was evaluated by DPPH radical scavenging activity. In vitro anti-inflammatory activity was estimated. Compounds 4d, 4e, 5b, and 5d showed the highest anti-inflammatory activity. The COX-1, COX-2 and 5-LOX inhibitory activities were measured using enzyme immune assay (EIA) kits. Due to the dual COX-2/5-LOX inhibitory activity of compound 5d, its cardiovascular profile was determined by measuring cardiac biomarkers (LDH, CK-MB, and Tn-I). Besides, the histopathological study of the heart muscle and stomach were examined for the most active COX-2 inhibitors 4e and 5d . Finally, a molecular modelling study and pharmacokinetic properties were obtained using different computational methods. Graphical abstract: UF0001